The Mnemonic Capitula Euangeliorum and Its Continuation in the Fifteenth-Century Manuscript Prague, National Library, VI D 21 - Dinkova-Bruun, Greti (Sacris erudiri, 2023)
This contribution represents a continuation of an article published in Sacris Erudiri in 2009. The first article contained an edition and a study of a mnemonic poem called Capitula Euangeliorum, whose versifying approach is to dedicate one hexameter to one biblical chapter, choosing words from the biblical text in the precise order they appear in it. Previously, the Capitula was known to exist in two manuscripts, Copenhagen, Royal Library, Thott 3 8vo and Vienna, ÖNB, Ms. 4543. Now a third witness has been discovered (Prague, National Library of the Czech Republic, Ms. VI D 21), in which the Capitula is expanded, covering the remaining books of the New Testament. The present article comprises two sections: first, an updated version of the Capitula Euangeliorum, and second, a first edition and a short study of the new verses found in the Prague manuscript.